Cell cycle regulation of chromatin at an origin of DNA replication - Zhou, Jing; Chau, Charles M; Deng, Zhong; Shiekhattar, Ramin; Spindler, Mark-Peter; Schepers, Aloys; Lieberman, Paul M (The EMBO journal, 2005)
Selection and licensing of mammalian DNA replication origins may be regulated by epigenetic changes in chromatin structure. The Epstein–Barr virus (EBV) origin of plasmid replication ( OriP ) uses the cellular licensing machinery to regulate replication during latent infection of human cells. We found that the minimal replicator sequence of OriP , referred to as the dyad symmetry (DS), is flanked by nucleosomes. These nucleosomes were subject to cell cycle‐dependent chromatin remodeling and histone modifications. Restriction enzyme accessibility assay indicated that the DS‐bounded nucleosomes were remodeled in late G1. Remarkably, histone H3 acetylation of DS‐bounded nucleosomes decreased during late G1, coinciding with nucleosome remodeling and MCM3 loading, and preceding the onset of DNA replication. The ATP‐dependent chromatin‐remodeling factor SNF2h was also recruited to DS in late G1, and formed a stable complex with HDAC2 at DS. siRNA depletion of SNF2h reduced G1‐specific nucleosome remodeling, histone deacetylation, and MCM3 loading at DS. We conclude that an SNF2h–HDAC1/2 complex coordinates G1‐specific chromatin remodeling and histone deacetylation with the DNA replication initiation process at OriP .